Our Project - Gatdula, Anna B. (Current Musicology, 2021)
This colloquy, by graduate-student-led collective Project Spectrum, attempts to map out existing discussions around inclusion and equity in music academia, with a specific focus on identifying and analyzing the structures in academia that work against minoritized and historically excluded scholars.